Weeds in agricultural and non-agricultural systems: Media influence, impacts and trends for a better systematic control against alternate and collateral hosts of crop pests - Kasonta, A A; Thakur, S S; Shaifali; Shukuru, B (Plant Science Today, 2025)
Weeds significantly impact agricultural productivity and environmental health by competing with crops for resources and acting as alternate hosts for pests. This study uniquely combines an ecological inventory with quantitative assessments to address weeds’ role in various ecosystems, including agricultural and non-agricultural areas such as roadsides and industrial sites. Methods included field surveys, species identification, and indices like informant consensus factor (ICF) and use value (UV) to measure weed prevalence, competition and adaptability. Results highlight that species like Cyperus rotundus and Echinochloa spp. pose substantial threats, causing up to 70% yield loss in specific regions, particularly in tropical irrigated crops. Additionally, weeds cause water loss, soil depletion, and habitat disruption in non-agricultural zones. This study emphasizes the need for integrated control strategies, combining cultural, mechanical, and chemical approaches. Media influence is also discussed, stressing its role in public perception and policy development for sustainable weed management. This work provides novel insights for enhancing agricultural resilience and environmental sustainability through improved weed control.